Effect of Physical, Chemical and Physiochemical Treatments of Surface Sterilisation on Medicinal Plants Salvadora persica and Solanum surattense for In-vitro Propagation - Naqvi, Beena; Mehboob Ali, Saleema; Makhani, Kiran; Yousuf, Kamran (Biological Sciences - PJSIR, 2017)
Effect of various surface sterilisation treatments on medicinal plants Salvadora persica and Solanum surattense has been studied for in-vitro propagation. Surface sterilisation treatment was applied by physical, chemical and physiochemical means. Chemical sterilisation was done with sodium hypochlorite, physically with sonication and physiochemically with combination of both. Sodium hypochlorite alone was found to be effective for smooth textured plant i.e., Salvadora persica, whereas for rough textured plant Solanum surattense a combination of both physiochemical means yielded good results. However, sonication alone did not render the effective way of surface sterilisation. Moreover, for Salvadora persica, 10% sodium hypochlorite was effective in eliminating bacterial or fungal growth whereas in Solanum surattense, a concentration of 15% sodium hypochlorite proved to be effective. In general, best results were achieved in the combined treatment by physiochemical means.